ANALISIS PENGARUH HARGA, PROMOSI, DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA RENTAL MOBIL DI SURAKARTA - C. Hendratmoko & Hestin Mutmainah, Budi Istiyanto (Universitas Slamet Riyadi, 2014)
Today, the competition of business in the world is increasing rapidly. The requires businesses to be creative and innovative to find a solution and the strategy for competitive advantage. The Car rental company in Surakarta having various strategies to influence the purchasing decisions of costumers, the strategies are competitive price, using a variety of media for promote their business, and improving quality of service to costumers. The satisfaction of costumers will affects against for more using with car rental services in Surakarta. This study aimed to investigate the influence of price, promotion and service against purchasing decision of car rental in Surakarta. This research was conducted by customer of car rental in Surakarta with one year period. The research sample was taken 120 respondents with accidental sampling. Techniques of data analysis used multiple linear regression. Keywords: price, promotion, services, purchase decision